Preliminary Studies of Thermal Wavelength Approximation in 208Pb and 91Zr hot Nuclei - Kurniadi, R. (ITB Journal Publisher, LPPM ITB, 2006)
Level density parameters of 208Pb and 91Zr in equilibrium states have been calculated with a new fugacity approximation namely a thermal wavelength approximation. In this approximation, the fugacity is directly proportional to the nucleon density. In contrast with the constant fugacity, the thermal wavelength approximation gives a simpler way to calculate the nuclei constant radius and the density profile. The calculated 208Pb nuclear density is about 0.17 (fm-3) in which the discrepancy is 0.1% higher than the experimental one. The level density parameters are 14% higher than the experimental results due to neglecting of the shell correction.